She [videorecording (DVD)] - Baker, Aimée; Mulgrew, Kate, 1955-; Goodwin, Raven, 1992-; Jones, Coco, 1998- (Gravitas Ventures, 2022)
Every year, 300,000 women go missing in the United States. How many of their names are remembered? Award-winning poet Aimě Baker is on a quest to honor these women and make sure their stories are not forgotten.